Tari Kreasi Ngelinyar - Ni Luh Putu Eka Wahyuningsih; Ni Made Arshiniwati; A.A.Ayu Mayun Artati (Jurnal IGEL : Journal Of Dance, 2021)
The creative source of this dance work comes from the creator's personal experience by seeing firsthand how the character Liku dances on stage in such a unique and eccentric style and has had several opportunities to support the dance test at ISI Denpasar. The experience gave the creator an idea to create a dance work that shows how bright female characters is klinyar. The word klinyar has meanings, namely nglinyar which means lively and maklinyaran which means flirty, with a special view of girls. The process of realizing it into a dance work using the method of creation by applying the principles of angripta-sesolahan, among others: ngarencana (exploration), nuasen (ceremony before the improvisation process), makalin (improvisation), nelesin (forming), and ngebah (first performance). This dance work is packaged in the form of creative dance, with the theme of social life, which is danced by six female dancers. The selection of dancers is adjusted to the creator's body posture. The accompaniment music uses the Semara Pagulingan barungan combined with the strains of the gerong sound to make the musical atmosphere more memorable. The realization of this dance work is expected to provide awareness on how to judge someone not only from the outside, but it is better if we also know how the character is inside.Keyword : character, Liku, klinyar, creation.